Three new species of trigonopoid Platynotina (Tenebrionidae: Pedinini) from the Baviaanskloof Nature Reserve, South Africa - Kamiński, Marcin Jan (Zootaxa, 2017)
Three new species representing closely related genera of the trigonopoid Platynotina are described from the Baviaanskloof Nature Reserve in South Africa: Atrocrates kandai sp. nov., A. smithi sp. nov. and Schelodontes baviaanskloofensis sp. nov. Based on newly acquired material, the taxonomic concept of Atrocrates is verified. Phylogenetic relationships between Atrocrates and Schelodontes are briefly discussed.